Twitter for good : change the world one tweet at a time - Diaz-Ortiz, Claire, 1982- (Jossey-Bass, 2011)
The official word from Twitter on how to harness the power of the platform for any cause. As recent events in Japan, the Middle East, and Haiti have shown, Twitter offers a unique platform to connect individuals and influence change in ways that were unthinkable only a short time ago. In Twitter for Good, Claire Diaz Ortiz, Twitter's head of corporate social innovation and philanthropy, shares the same strategies she offers to organizations launching cause-based campaigns. Filled with dynamic examples from initiatives around the world, this groundbreaking book offers practical guidelines for harnessing individual activism via Twitter as a force for social change. Reveals why every organization needs a dedicated Twitter strategy and explains how to set one Introduces the five-step model taught at trainings around the world: T.W.E.E.T. (Target, Write, Engage, Explore, Track) Author @claired is the head of corporate social innovation and philanthropy at Twitter, working with organizations like Nike, Pepsi, MTV, the American Red Cross, charity:water, Room to Read, the Gates Foundation, the Skoll Foundation, the Case Foundation, National Wildlife Federation, Kiva, the United Nations, Free the Children, Committee to Protect Journalists, Partners in Health, FEMA, Ushahidi, The Acumen Fund, TED With more than 200 million users worldwide, Twitter has established itself as a dynamic force, one that every business and nonprofit must understand how to use effectively"--